SMART TECHNOLOGIES DI SUPERMARKET RETAIL DAN PENGARUHNYA TERHADAP KUALITAS HIDUP MASYARAKAT SELAMA PANDEMI COVID-19 - Cindy Farahita; Kurniawati Kurniawati (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The presence of smart technology allows consumers to go to supermarkets and complete transactions without having to go to the supermarket. The competitive, innovation-driven retail industry includes an ever-evolving array of companies that are continually impacted by a highly diverse and dynamic environment. This research aims to propose the development of a model inidentifying essential services, the determinants influencing the technological advances offered by different smart technologies in supermarkets retail that affect the quality of life the community during the COVID-19 pandemi. The design/methodology used data collected using a questionnaire survey (n=308). The method used non-probability sampling with purposive sampling technique. The results of the study or findings provides a more complex view that engagement has an important role in influencing people's quality of life. If consumers return to old habits, new regulations, and procedures are likely to change the way people buy products and services with the advancement of smart technologies in supermarkets retail